Fluid mechanics for chemical engineers - De Nevers, Noel 1932-; Silcox, G. D. (Geoffrey Damian) (New York McGraw-Hill Education, 2021)
This book presents an introduction to fluid mechanics for undergraduate chemical engineering students. Throughout the text, emphasis is placed on the connection between physical reality and the mathematical models of reality, which we manipulate. The book is divided into four sections. Section I, preliminaries, provides background for the study of flowing fluids. Section II discusses flows that are practically one-dimensional or can be treated as such. Section III discusses some other topics that can be viewed by the methods of one-dimensional fluid mechanics. Section IV introduces the student to two- and three-dimensional fluid mechanics
Keywords: Chemical engineering; Fluid mechanics